Detection and isolation of bacteria affected by dietary cumin, coriander, turmeric, and red chili pepper in the caecum of ICR mice. (October 2019) - Xia, Yumeng; Kuda, Takashi; Toyama, Ai; Goto, Minori; Fukunaga, Mayu; Takahashi, Hajime; Kimura, Bon
Graphical abstract: Highlights: Effects of the spices on the caecal microbiota were revealed by 16S rDNA amplicon sequencing. Several OTUs were estimated as the spice-susceptible indigenous gut bacteria (S-SIB). Among S-SIB, B. pseudolongum, L. jouhnsonii, L. murinus, and Cl. innocuum could be isolated. Abstract: Some food ingredients are thought to be correlated with the gut microbiome. To clarify the presence of susceptible gut indigenous bacteria (SIB) against four popular spices, ICR mice were fed with a high-sucrose diet containing no-fibre (NF), 2% w/w cumin-seeds (CM), coriander-seeds (CR), turmeric (TM), or red chili pepper (RP) for seven days. The caecal microbiome was examined by 16S rDNA amplicon sequencing using a MiSeq system. Principal coordinate analysis of operational taxonomic units (OTUs) revealed microbiome alterations in the CM, CR, and RP groups. Typical SIB in the CM, CR, TM, and RP groups were Bacteroides acidifaciens- and Bacteroide sartorii -like, Lactobacillus johnsonii -like, Bifidobacterium pseudolongum -like, and RP-SIB Lactobacillus murinus –like bacteria, respectively. [ Clostridium ] innocuum - and Faecalibaculum rodentium -like bacteria were suppressed by the spices. Of the SIB identified, B. pseudolongum, L. johnsonii, L. murinus, and [ Clostridium ] innocuum were isolated and identified using BL agar and a 16S rDNA BLAST search, respectively.